HEALTH EDUCATION IN THE PREVENTION OF INFECTIONS IN HEMODIALYSIS PATIENTS: AN EXPERIENCE REPORT - de Carvalho, Lucas Pereira; Melo, Stephanie Lorrane Fernandes; da Silva, Élida Maria; da Silva, Bruno Henrique; dos Santos, Laís Tavares; Batista Filha, Ana Júlia Andrade; Nunes, Poliana Lucena; Martins, José Luís Rodrigues; Pinto, Emerith Mayara Hungria; Costa, Murilo Marques; Gomes, Fabiana Silva (Seven Editora, 2026)
Hemodialysis is an indispensable therapy for patients with advanced chronic renal failure, but it is associated with high risks of infections, especially those related to vascular access. The objective is to report on the experience of an extension project focused on health education for the prevention of infections in patients undergoing hemodialysis. This is an experience report developed within the scope of the Body Fluids and Urinalysis course, part of the Biomedicine program at a university in the interior of the state of Goiás. The activities were carried out in person at a nephrology institute during hemodialysis sessions in the morning and afternoon shifts over two days, involving students, a supervising professor, and patients undergoing treatment. The educational activities included a dialogue-based presentation on infection prevention, vascular access care, and hand hygiene, as well as dynamic activities, such as an educational true-or-false game and a practical demonstration of hand hygiene techniques using playful resources. The results showed high patient participation and engagement, promoting understanding of guidelines and knowledge exchange in the care environment itself. The experience also enabled students to articulate theory and practice, develop health education skills, and gain a greater understanding of the complexity of hemodialysis care. It is concluded that educational actions carried out in the context of dialysis treatment are a relevant strategy for promoting patient safety, preventing infections, and strengthening integration between the university and the community. DOI: https://doi.org/10.56238/sevened2026.001-001